Percepções de gênero nas escolas atendidas pelo PROERD: um estudo a partir dos relatos de professor@s (São Leopoldo/RS) - Oliveira, Arlindo Weber de (2014)
This research aims to examine, from the reports of teacher, perceptions of gender in schools served by PROERD schools in the city of São Leopoldo /RS, in 2013, committed by students in a school environment. The methodological approach involved conducting a survey qualitative, observations where seven semi-structured interviews were conducted. From the content analysis of systematic data the following categories were highlighted: Bias of teachers in terms of gender, the hidden curriculum, bullying and homophobic bullying. Results showed evidence of difficulty, from the perception of teachers, manifestations of violence gender, explicit and implicit, in schools during the study period. Such aspects as well as the categories that stood out in the analysis can be linked to lack of teachers' perception about gender violence. It may be conjectured two reasons for which can be determined "perceptual dulling": lack of teacher knowledge about "gender violence", and prejudices of teachers with regard to sexuality. If these reflections have a grain of truth, the results indicate that the situation may prove even more serious insofar as manifestations of gender violence in schools may be happening, but are not being perceived / identified by these teachers and, consequently, the school is not dealing with them adequately.